Twelfth night, or, What you will - Shakespeare, William, 1564-1616; Bloom, Harold (Shakespeare, William, 1564-1616. Works. 2003., 2007)
Twins Viola and Sebastian are shipwrecked. Believing her brother drowned, and determined to survive alone, Viola disguises herself as a boy. As 'Cesario' she enters the service of Orsino and is sent by him to woo Olivia. But Olivia isn't interested and 'Cesario' is swept into a merry-go-round world of unrequited love, mistaken identities, high comedy, low tricks and desperate passion. --Publisher.